Assessment of Antiretroviral Treatment Adherence among Children Attending Care at a Tertiary Hospital in Southeastern Nigeria - Cletus Akahara; Emeka Nwolisa; Kelechi Odinaka; Seline Okolo (Journal of Tropical Medicine)
Background. Adherence is the strongest predictor of successful treatment outcome among children infected with HIV. Our aim was to assess the antiretroviral drugs adherence status of HIV-infected children attending care at a tertiary hospital in Southeastern Nigeria. Method. The study involved a cross-sectional survey of 210 HIV-infected children attending care at a tertiary hospital in Southeastern Nigeria using self-report method of assessment. Optimal ART adherence is defined as patient taking not missing more than 1 dose of combined antiretroviral therapy medication in the preceding 2 weeks prior to the study. Result. A majority of the subjects 191 (91%) had good adherence. There was a significant relationship between adherence and patient educational level (p=0.004), duration of treatment (p=0.001), drug administrator (p=0.005), and orphan status (p=0.001). The motivating factor for adherence was “not falling sick as before” while stigma was the most discouraging factor. Conclusion. The adherence level in this study was good. Stigma was an important reason given by patient/caregivers for nonadherence. There is need for concerted effort in addressing this barrier to improve adherence and prevent the emergence of drug resistance and treatment failure.